Generation Z students perception on instruction in ICT class: a case study of Sekolah Menengah Kg Jawa, Klang / Normazhazlin Alzahari - Alzahari, Normazhazlin (2011)
Malaysia’s Ministry of Education has taken a big step to embrace globalization by using information communication technology (ICT) as one of it’s’ subject to stay relevant and to make sure that their younger generation is not left behind. Known as in ICTL (Information and Communication Technology Literacy), the subject is a nonexam subject and is taught to students aged 13 and 14 from form 1 and 2 students as an introduction to ICT. Sekolah Menengah Kebangsaan Kampung Jawa, Klang Selangor was chosen by the researcher because it has a large computer laboratory with more than 30 P.C’s for the students to use without sharing it. Understanding the importance of effective communication, the researcher decided to investigate the Generation Z student’s perception on the instruction in ICTL class within the school based on the constructivist approach in teaching where the teacher is seen as a knowledgeable and skillful in order to promote understanding. A questionnaire surveyed and distributed to middle age group of Generation Z students represented by the form 1 and 2 students to understand their perception on the instruction in ICTL class. A mixed method analysis was used to determine the distribution of respondents across the students. Personal background and factors relating to students’ technology usage were also taken into consideration to better understand the factors that contribute to this distribution. Through the findings, the researcher concluded that through the Generation Z student’s perception, teacher’s instruction in their ICTL classes, teacher’s ICT skills and the ICT facilities in their computer labs are very important for an effective communication in their ICTL classes. Lastly, this investigation produced recommendations that can further enhance the ICT policy in schools.